Potensi Menir sebagai Alternatif Sumber Bahan Baku pada Pengembangan Produk Makanan Berbasis Tepung Beras : Systematic Review (Journal of Vocational Innovation, Achievement and Education, 2025)
Rice is a major agricultural commodity widely cultivated in Indonesia. During the rice milling process, three forms of rice are produced: whole rice (premium quality), broken rice, and menir (rice fragments). Based on field observations and literature reviews, menir remains underutilized due to its less appealing physical appearance. This review aims to identify the physicochemical properties of broken rice (menir) and explore its potential derivative products based on studies reported in relevant journals. The method used is a systematic review, gathering information from online article publications available on platforms such as Google Scholar, ScienceDirect, and Scopus. The results indicate that menir has significant potential for further processing, with characteristics similar to whole rice in terms of physical and nutritional properties. Menir contains 8.18% protein, 1.07% fat, 89.81% carbohydrates, 12.45% moisture, 0.94% ash, and 2.13% fiber. It can be processed into both intermediate and final (finished) products. Product development from menir includes wet and dry cakes, as well as functional analog rice, by combining it with ingredients rich in specific nutrients for fortification, thus offering functional food properties. In the future, menir can be further explored as a raw material for innovative product development in various research areas.
Keywords: Menir; sifat fisikokimia; tepung beras